2016
DOI: 10.1016/j.vaccine.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological impact and cost-effectiveness of universal vaccination with Bexsero® to reduce meningococcal group B disease in Germany

Abstract: Bexsero, a new vaccine against serogroup B meningococcal disease (MenB), was licensed in Europe in January 2013. In Germany, Bexsero is recommended for persons at increased risk of invasive meningococcal disease, but not for universal childhood vaccination. To support decision making we adapted the independently developed model for England to the German setting to predict the potential health impact and cost-effectiveness of universal vaccination with Bexsero(®) against MenB disease. We used both cohort and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 24 publications
3
56
0
Order By: Relevance
“…Although other studies cannot be directly compared to ours due to, e.g., diverging reimbursement practices in different countries, differences regarding study design, and IMD case definitions and study populations, most revealed substantial short-term excess costs associated with IMD as observed in our study. Christensen et al [34] derived the costs of acute IMD episodes from the diagnosis related group system used for inpatient billing in Germany in 2013 and estimated costs of € 5,045 and € 4,798 per IMD case aged < 16 years and 16+ years, respectively. However, the actual mean hospital costs in our study were substantially higher with costs of € 9,620.…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies cannot be directly compared to ours due to, e.g., diverging reimbursement practices in different countries, differences regarding study design, and IMD case definitions and study populations, most revealed substantial short-term excess costs associated with IMD as observed in our study. Christensen et al [34] derived the costs of acute IMD episodes from the diagnosis related group system used for inpatient billing in Germany in 2013 and estimated costs of € 5,045 and € 4,798 per IMD case aged < 16 years and 16+ years, respectively. However, the actual mean hospital costs in our study were substantially higher with costs of € 9,620.…”
Section: Discussionmentioning
confidence: 99%
“…Although vaccinating a cohort of 150,000 infants could be expected to (Pouwels et al 2013), Italy (Gasparini et al 2016), England , and France (Lecocq et al 2016) all found an infant immunization program not to be cost-effective. However, when the authors of the English study included more "favourable" assumptions, including quality-of-life losses for family and network members, 1.5% discounting, and the value of litigation costs, results showed that a routine infant vaccination could be cost-effective with a lower vaccine price (Christensen et al 2016). In our analysis, in order to obtain a cost per QALY of $135,000 (considered the highest limit of cost-effectiveness according to the WHO guidelines (Walker et al 2010)), the disease incidence would have to be 4.65 times higher (even more if using the most recent data (Public Health Agency of Canada 2017)) or a vaccine price of $11 per dose.…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study of infants in the UK estimated a 2-dose MnB vaccine effectiveness of 82.9% against MnB cases (Parikh et al 2016), while a UK model estimated 95% MnB vaccine efficacy to prevent IMD among carriers (Christensen et al 2016). A 75% to 100% seroresponse rate in adolescents was reported in clinical trials of a 2-dose regimen of the MenB-FHbp vaccine (Vesikari et al 2016).…”
Section: Vaccine Efficacymentioning
confidence: 99%
“…The JCVI has applied a QALY adjustment factor (QAF) of 3 (relevant QALY gains are multiplied by 3) [18] to long-term sequelae associated with MenB IMD, which was employed in 2 studies identified in the literature search. Studies of HU loss typically address only the patient and his or her sequelae, but more recent assessments have included QALY losses for caregivers to reflect the wider impact of IMD on the network of individuals surrounding the patient [13,19].…”
Section: Literature Review: Rapid Evidence Assessmentmentioning
confidence: 99%
“…A number of recent cost-effectiveness estimates of vaccines targeting serogroup B IMD have been outside the range of acceptable willingness-to-pay for a quality-adjusted life-year (QALY) threshold using standard methods. However, methods vary among countries (which can lead to differing conclusions among decision-making bodies), and it has been argued that standard approaches may not fully capture the impact of vaccines [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%